2022
DOI: 10.1002/celc.202200900
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Electronic Structure of Active Centers in Metalloporphyrins to Boost Oxygen Reduction Reaction Activity

Abstract: Inspired by the ligand‐promoted high reactivity of the heme active center in cytochrome c oxidase (CcO) toward oxygen reduction reaction (ORR), this work proposes a new strategy for improving the efficiency of metalloporphyrin‐catalyzed ORR. We carried out a comparative study between two graphene/cobalt porphyrin complexes, the rGO/TMPPCo formed by noncovalent π‐π stacking, and the rGO‐Ci/TMPPCo with cobalt porphyrins (TMPPCo) axially coordinated with the 1‐carboimidazole (Ci) ligands on reduced graphene oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The octahedral structures are formed by the sixth coordination of the O 2 *, OOH*, O*, and OH* intermediates. By coordinating the ligands, a central metal ion with a smaller positive charge promotes the activation of O 2 and results in the elongation of the O=O bond length 60 . The percentages of occupied states of Co atoms in Co‐NrGO‐1 and Co‐NrGO‐2 is 73.3% and 73.6%, respectively, indicating that Co atoms in Co‐NrGO‐2 are less positive (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The octahedral structures are formed by the sixth coordination of the O 2 *, OOH*, O*, and OH* intermediates. By coordinating the ligands, a central metal ion with a smaller positive charge promotes the activation of O 2 and results in the elongation of the O=O bond length 60 . The percentages of occupied states of Co atoms in Co‐NrGO‐1 and Co‐NrGO‐2 is 73.3% and 73.6%, respectively, indicating that Co atoms in Co‐NrGO‐2 are less positive (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…By coordinating the ligands, a central metal ion with a smaller positive charge promotes the activation of O 2 and results in the elongation of the O=O bond length. 60 The percentages of occupied states of Co atoms in Co-NrGO-1 and Co-NrGO-2 is 73.3% and 73.6%, respectively, indicating that Co atoms in Co-NrGO-2 are less positive (Table S11). The bond lengths of adsorbed O 2 to Co-NrGO-1 and Co-NrGO-2 are 1.287 and 1.294 Å, respectively, which are longer than those of a free O 2 molecule (1.234 Å).…”
Section: Theoretical Calculation For Orr Mechanismmentioning
confidence: 99%
“…[94] Electron-donating trans axial ligands, being introduced from either the direct covalently coupling or the secondary coordination sphere at the meso-positions, can improve ORR activity and selectivity by facilitating oxygen binding and activation through the electronic "push effect", by which the electrophilic attack of a proton to the metal center becomes more favored. [95,96,97] A density functional theory (DFT) study on an iron porphyrin 26 in Figure 8 bearing both acid releasing group and axial imidazole ligand suggested that the carboxylic acid group can (de)stabilize the FeÀ O bonding by forming hydrogen bonds with the adsorbed reaction intermediates, while the axial ligand raised the affinity of the iron-bound super-oxo and per-oxo ligands for proton as well as stabilized a key precursor for OÀ O bond cleavage, thus leading to remarkable 4-electron selectivity and positive reduction potentials for the ORRs. [98] Similar findings were also reported for some other iron porphyrins 27-29 with pendant guanidine ligand at their meso-positions, which exhibited improved 4electron selectivity by attaching axial imidazole ligands (Figure 8).…”
Section: Electron Affinity Of Substituentsmentioning
confidence: 99%
“…In addition to meso ‐substituents, the atomic charge of the metal center and the electronic structure of the ligand systems can be controlled by axial ligands, in particular, the trans ‐positioned ones, which affect the back‐bonding formation between the metal ion and dioxygen, and in consequence the activation process [94] . Electron‐donating trans axial ligands, being introduced from either the direct covalently coupling or the secondary coordination sphere at the meso ‐positions, can improve ORR activity and selectivity by facilitating oxygen binding and activation through the electronic “push effect”, by which the electrophilic attack of a proton to the metal center becomes more favored [95,96,97] . A density functional theory (DFT) study on an iron porphyrin 26 in Figure 8 bearing both acid releasing group and axial imidazole ligand suggested that the carboxylic acid group can (de)stabilize the Fe−O bonding by forming hydrogen bonds with the adsorbed reaction intermediates, while the axial ligand raised the affinity of the iron‐bound super‐oxo and per‐oxo ligands for proton as well as stabilized a key precursor for O−O bond cleavage, thus leading to remarkable 4‐electron selectivity and positive reduction potentials for the ORRs [98] .…”
Section: Porphyrin Structural Effects On Orr Performancementioning
confidence: 99%
“…[18][19][20][21][22] By implementing such strategies, the adsorption modes of oxygen can be altered, thereby favoring the 4-electron oxygen reduction pathway. The second approach is to regulate the substituents on the porphyrin ring, including modifications at either meso-or β-positions, or both, in order to realize certain benefits, such as optimization of the electron density distribution particularly around the metal core, [23][24][25] introduction of proton relay or management effects, 26,27 use of additional substituent functions like steric effects and triphenylamine (TPA) merits, 28,29 and the interaction strength between the porphyrin and the support material. 12,[30][31][32] One potentially effective approach in the molecular engineering of porphyrin substituents is the tuning of the symmetry of metalloporphyrins.…”
Section: Introductionmentioning
confidence: 99%